MENINGKATKAN PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI DALAM MENGENAL KONSEP BILANGAN MELALUI PENERAPAN MODEL MAKE A MATCH - Hevie Setia Gunawan; Imas Kurniasih; Mega Nurhayati; Ayu Puji Rahayu (Jurnal Al Burhan, 2022)
The concept of numbers is the basis of mathematics which consists of counting numbers, connecting objects, knowing the number of objects, based on initial observations there are still many children who seem to be less focused on the material that has been delivered by the teacher and some cannot even name the order of numbers from one to ten which are not sequential spoken. The purpose of this research is to increase understanding of the concept of numbers by applying the Make a Match model at RA Al-Karomah, Karangtanjung Village, Cililin District, West Bandung Regency. In this study using classroom action research which consists of stages, implementation stages, observation stages and reflection stages which consist of 2 cycles. The results of this study show an increase in the ability to recognize the concept of numbers in group A children at RA Al-Karomah. Data from the research results regarding the concept of numbers applying Make a Match are presented as follows: in Cycle I after the first meeting was held the result was that the criteria had not developed by 33.33%. Criteria began to develop at the first meeting 58.33%, the second meeting 66.67%. The criteria developed according to the expectations of the first meeting 8.33% and at the second meeting it became 33.33%. Furthermore, there are no well-developed criteria. Cycle II on undeveloped criteria does not exist. Criteria for starting to develop does not exist. The criteria that developed as expected at the first meeting were 75%, then became 41.67%. The criteria developed very well at the first meeting of 25%, the second meeting became 58.33%. So from these results it can be concluded that the understanding of the concept of numbers can be improved by using Make a Match.